Pengaruh Profitabilitas, Ukuran Perusahaan dan Leverage Pada Perusahaan Manufaktur Sektor Makanan & Minuman Terhadap Tax Avoidance - Putri, Melansa; Nuryati, Tutty; Rossa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (CV. Lafadz Jaya, 2023)
The purpose of this study is to find dan analyze theories regarding the effect of profitability, company size, dan leverage on tax avoidance. This research uses the literature review method. In this study, researchers analyzed dan explained variables from other literature findings. The theories used in this study are agency theory dan behavioral theory (TPB). The results stated that profitability, company size, dan leverage in food dan beverage sector manufacturing companies have a positive effect on tax avoidance.